O impacto do capital psicológico e da confiança organizacional sobre o desempenho no trabalho - Vaz, Caroline Maria Fonseca Rocha (2013)
This study aimed to verify the predictive power of the variables psychological capital and organizational trust on job performance evaluated on two dimensions: proactive performance and task oriented performance. The study included 211 employers formally linked to different organizations of work, mostly male (58.3%), mean age 30 years old (SD = 9.3) and average working time equal to 5.34 years (SD = 6.19). The predominant level of education is high school degree (32%) The instruments used were valid and reliable for each construct for data collection, with Cronbach\'s Alpha exceeding 0.70. The reliability of the scales for the study s sample showed coefficients above 0.70. We calculated the standard multiple regression analysis, using as dependent variables the proactive performance and the task oriented performance and as independent variables, the psychological capital and the organizational trust. The results indicated that the both, task oriented performance and proactive performance showed positive and significant correlations with psychological capital, trust in organizational competence, and ethical standards. Regression analyzes indicated the psychological capital as a significant predictor of task oriented performance and proactive performance showing 23.8% and 35.1% of variance, respectively. In both cases the contribution of trust was not significant, causing the exclusion of the models. Therefore, the proposed model wasn t confirmed. It is recommended for future research, the evaluation of trust as mediating or moderating variable in the relationship between psychological capital and job performance. This study presents contributions to the academic field to investigate the variables in an integrated model and in terms of people management to consider the importance of individual variables in employee performance.